'Hell You Talmbout': Janelle Monáe's Black Cyberfeminist Sonic Aesthetics. Issue 1 (March 2021) - Yates-Richard, Meina
This article explores the ways in which Janelle Monáe's audiovisual performances leverage black female flesh to trouble historically constituted imaginings of 'the human'. Tracking Monáe's audiovisual aesthetics across 'Many moons' and Dirty Computer, I interrogate acoustic and imagistic resonances that recall the repeating horrors of bondage, and which also constitute performative 'fabulations' whereby freedoms that are engendered specifically by and within black female flesh might be imagined. Monáe 'enfleshes' the cyborg to critique cyberfeminist and posthumanist theories that advocate for material dissolution as a framework for liberation, as well as to trouble black women's historical relationships to the category 'human'. Rather than understand Dirty Computer as a (re)turn to the human Monáe, I contend that the project extends the artist's longstanding critical engagement with the black female cyborg and black sonic cyberfeminist liberatory potentialities.